The impact of maternal employment on family members' perceptions and attitudes towards the maternal role - Santiago-de la Cruz, Alma (Philippine Journal of Psychology, 1986)
The effects of maternal employment on family members' perceptions of the mother, sex-role concepts of the children, and attitudes towards working women were studied using the survey and the case study method. One hundred male and female adults and 110 children participated in the survey. Four intact families were interviewed and observed for an extended period of study showed that employed women had the most favorable attitudes towards working women, followed by the unemployed women,and by the men regardless of whether their wives were employed or not employed. Children of employed mothers were also more egalitarian in their sex-role concepts than children of unemployed mothers. The former group perceived their mothers as more affectionate than the children of unemployed mothers.The case studies showed that maternal employment did not affect mother-child variables of nurturance and protectiveness, discipline, and independence training. This was explained in terms of the greater effect of cultural factors and the fact that children are the priority of both groups of mothers.